Fenomena Tarekat Dalam Tradisi Pesantren (Analisis Sosio Historis terhadap Perkembangan Tarekat dan Pesantren di Indonesia) - Saiful Mujab (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2019)
This project involves discovering how the spiritually tradition especially tarekat is exist in the pesantren in Indonesia. The goal of this research proves the phenomenon that pesantren and spirituality tradition are strongly linked and connected between each other. Several spiritualities in pesantren are; tarekat, tirakat, berkah, akhlaq/etic and others. This article is arranged based on library research and comparing several references by some books, articles and jurnals. Furthermore this research also takes some of statements, explanations, speeches and etc that related with this concern. Hopefully, this article will give a contribution to the discussion about tarekat, spirituality and pesantren in Indonesia.